Deep vein thrombosis risk stratification in intensive care unit patients: a pressing need - Patel, Viral B.; Ghosh, Labani M.; Vaishnav, Bhalendu (International Journal of Research in Medical Sciences, 2020)
Background: Risk stratification of deep vein thrombosis in patients admitted to ICU and incorporating DVT risk assessment score as a regular practice were the aim of the present study. Methods: This study was carried out in 67 patients admitted in ICU >18 years of age, over one year. Patients with confirmed DVT, <48 hours of stay, thrombocytopenia, diagnosed coagulation disorders, those who have received DVT prophylaxis in last 1 month and those with active bleeding were excluded. It was a cross sectional observational study. A SMART assessment score and pretest probability scoring card was used. Mechanical or pharmacological prophylaxis was given to those with moderate and high risk for DVT. Results: As per SMART assessment score 4.5%, 41.8%, 6% and 23.9% had no, moderate, high and highest risk of developing DVT. As per the pretest probability scores 76%, 20.9% and 3% were in low, moderate and high-risk group. Both scoring systems are comparable (p=0.001). There was significant association between paralysis (p value was 0.003), central venous access (p value was 0.006), patient bed ridden for >72 hours (p value was 0.009) and risk group. Conclusions: Prolonged bed rest, paralysis and central venous access are the most important contributing conditions for high risk of DVT. Risk stratification should be routinely performed in ICU. SMART assessment tool and pre-test probability scores are both equally efficacious in identifying high risk patients for DVT. Both mechanical and pharmacological means of DVT prophylaxis are equally effective in preventing DVT.